Pemilahan Limbah Plastik di Desa Mandor Kabupaten Landak - Dina Setyawati; Luhut Pardamean Manik; Muhammad Fahrul (Program Studi Pendidikan Guru Sekolah Dasar Universitas Flores Ende, 2026)
The increase in population and development across sectors has led to a growing volume of plastic waste that is difficult to decompose and can harm the environment. In Mandor Village, Mandor District, Landak Regency, the community already has a plastic shredding machine; however, its use remains suboptimal due to a lack of knowledge about plastic type separation. This Community Service Program (PKM) aims to enhance the community’s knowledge and skills in sorting plastic waste using simple methods, enabling it to be processed into economically valuable materials while supporting environmental sustainability. The implementation methods include socialization, education, and direct demonstrations of how to identify plastic types using scratch, flame, and immersion tests. Evaluation was conducted using questionnaires administered before and after the activity to assess participants’ understanding. The results showed a significant increase in the community’s knowledge of plastic types, sorting techniques, and business opportunities in plastic waste processing. The community demonstrated high enthusiasm and commitment to developing independent plastic recycling businesses. This PKM activity successfully increased the awareness and capacity of Mandor Village residents to manage plastic waste effectively, while opening new economic opportunities in the recycling sector. Recommended follow-up actions include digital marketing training and the development of a website to support the promotion and sale of recycled plastic products from Mandor Village.